2016
DOI: 10.1016/j.pediatrneurol.2016.03.011
|View full text |Cite
|
Sign up to set email alerts
|

PEHO Syndrome May Represent Phenotypic Expansion at the Severe End of the Early-Onset Encephalopathies

Abstract: BACKGROUND Progressive encephalopathy with edema, hypsarrhythmia and optic atrophy (PEHO) syndrome is a distinct neurodevelopmental disorder. Patients without optic nerve atrophy and brain imaging abnormalities but fulfilling other PEHO criteria are often described as a PEHO-like syndrome. The molecular bases of both clinically defined conditions remain unknown in spite of the widespread application of genome analyses in both clinic and research. METHODS We enrolled two patients with a prior diagnosis of PEH… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
22
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 26 publications
(22 citation statements)
references
References 19 publications
0
22
0
Order By: Relevance
“…[2][3][4][5]8,10,12,[14][15][16]26 MRI studies have not shown major structural abnormalities in patients with GNAO1 variants. Developmental delay and hypotonia occur in nearly all cases, although they led less frequently to medical attention.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…[2][3][4][5]8,10,12,[14][15][16]26 MRI studies have not shown major structural abnormalities in patients with GNAO1 variants. Developmental delay and hypotonia occur in nearly all cases, although they led less frequently to medical attention.…”
Section: Discussionmentioning
confidence: 99%
“…All 14 individuals had GNAO1 variants identified through clinical testing, either by whole exome sequencing (WES; 8,9,13,and 14) or by targeted next generation sequencing epilepsy panels (Patients 7 and 10-12). Parental testing was completed for all but one patient.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Since the original clinical description of this condition in 1991, a number of different genes and modes of inheritance have been associated with clinical presentations said to be consistent with PEHO, or thought to be PEHO-like in nature, including de novo dominant variants in CDKL5 and KIF1A and biallelic mutations in CCDC8A (Gawlinski et al , 2016; Langlois et al , 2016; Nahorski et al , 2016) . The phenotype in the Italian family, as well as consistent overlapping clinical aspects present in the other families described here, provides cause to consider that PRUNE1 should now also be added to the list of genes in which mutations may present in children with epileptic encephalopathy and PEHO-like features.…”
Section: Discussionmentioning
confidence: 99%